Treatment Palm Oil Mill Effluent (POME) Using Continuous Column Plate Electric Reactor - Susanto, Reno; Aulia Rahmi , Viona; Widyaningsih , Dwi (Al-Kimia, 2022)
Palm oil mills produce palm oil mill effluent (POME) which contains various dissolved organic compounds in the form of short fibers, hemicellulose, and their derivatives, protein, free fatty acids, a mixture of minerals and organic pigments such as anthocyanins, carotene, polyphenols, lignin and tannins. Organic compounds in this waste will cause problems such as increasing the value of TSS, TDS, and COD which can be a crucial environment for processing liquid waste in palm oil mills. One possible method to reduce the content of TSS, TDS, and COD is the electrocoagulation method. This study aims to determine the effect of variable flowrate, voltage, and distance between plates in the electrocoagulation process with a plate column electric reactor, and determine the optimum conditions for flowrate, voltage, and distance between plates. Optimum conditions are obtained at fflowrate3 L/min, 28 V voltage, 2 cm distance between plates with percent removal of TSS, TDS, and COD, respectively 49.30%; 49.40%; 60.30%.